2D TiN@C sheets derived from MXene as highly efficient polysulfides traps and catalysts for lithium−sulfur batteries. (10th July 2021) - Fan, Yepeng; Liu, Kaige; Ali, Asad; Chen, Xingfa; Shen, Pei Kang
Highlights: TiN@C/G is used as the separator coating for lithium-sulfur batteries. TiN@C sheets are synthesized by in-situ nitridation of 2D transition metal carbide MXene. TiN@C has strong chemical interaction with lithium polysulfides (LiPSs) and can promote their conversion to Li2 S2 /Li2 S. Graphene (G) acts as a conductive network and physical barrier. Abstract: Well known for their high energy density, lithium-sulfur (Li-S) batteries face the problem of rapid capacity degradation caused by the polysulfides (LiPSs) shuttling. By modifying the battery separator with specific materials, the shuttle effect can be effectively alleviated. Herein, two-dimensional (2D) TiN@C sheets obtained by in-situ nitridation of MXene (Ti3 C2 Tx, T means the termination groups, such as -F, -O, and -OH) are designed as the traps and catalysts for LiPSs in Li-S batteries. TiN@C has strong chemical absorptivity of LiPSs and can promote their conversion to Li2 S2 /Li2 S. By mixing with graphene, which servers as a conductive network and physical barrier, a TiN@C/G separator coating is fabricated via a vacuum filtration method. Based on the carbon black/sulfur (CB/S) cathode and TiN@C/G coated separator, the batteries deliver a surprising initial discharge capacity at 0.1 C (1490.2 mAh g −1 ) and show a extremely low capacity loss over 600 cycles at 1 C (0.047% per cycle). This work shows new views into the design of separator coating using 2D materials for Li-S batteries with high capacity and stability. Graphical abstract: TiN@C sheets were synthesized by in-situ nitridation of Ti3 C2 Tx Mxene and then mixed graphene (G) as the separator coating for high-performance Li-S batteries Image, graphical abstract .